2022
DOI: 10.1177/20563051221077217
|View full text |Cite
|
Sign up to set email alerts
|

Disconnection: How Measured Separations From Journalistic Norms and Labor Can Help Sustain Journalism

Abstract: This commentary considers the concept of “disconnection” as a way to understand practices of contemporary digital journalism while advocating for consideration of disconnection as a necessary component of sustainable journalism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…What is useful about this particular strategy is that it allows the viewer to feel heard and allows for them to communicate any errors that potentially were in the story while also protecting the reporter's time and wellbeing by not submitting to the hostility. Tips like this could be easily shared in basic reporting classes, and is in line with research that positions disengaging as a core skill for journalists (Bélair-Gagnon et al, 2022;.…”
Section: Preparing Students For Hostility: Some Classroom Starting Po...supporting
confidence: 54%
See 1 more Smart Citation
“…What is useful about this particular strategy is that it allows the viewer to feel heard and allows for them to communicate any errors that potentially were in the story while also protecting the reporter's time and wellbeing by not submitting to the hostility. Tips like this could be easily shared in basic reporting classes, and is in line with research that positions disengaging as a core skill for journalists (Bélair-Gagnon et al, 2022;.…”
Section: Preparing Students For Hostility: Some Classroom Starting Po...supporting
confidence: 54%
“…Whenever students are asked to share their content online (for class via social media platforms, self-publishing sites such as Medium.com, or even in the case of student media), a discussion should follow about the hostility that can arise in online spaces. Students should be taught best practices for engaging with audiences online, how to lock down their personal information to protect themselves from trolls, and, modeling Bélair-Gagnon et al (2022) and Bossio and Holton (2021), advice for avoiding burnout and learn disconnection strategies. 3.…”
Section: Preparing Students For Hostility: Some Classroom Starting Po...mentioning
confidence: 99%
“…When we put the user- and journalistic perspectives next to each other, we can find similarities in the causes of reluctance, such as dark participation and the risk of reputational damage (Bossio and Holton, 2021; Bélair-Gagnon et al, 2022). Journalists could take a pioneering role in creating conditions for interaction, favorable for both parties, to ensure a useful and sustainable relationship.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However, according to Vos and Ryan (2023), the discourse among journalists has shifted from audience engagement as vital for their future to concerns about their wellbeing, threatened by online harassment and other forms of ‘dark participation’ (Bélair-Gagnon et al, 2022; Holton et al, 2021). Journalists are experiencing burnout and different forms of social media fatigue (Bossio and Holton, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This study builds off of previous work that has observed the problems inherent in journalists' use of social media (e.g., Bélair-Gagnon et al, 2022;Holton et al, 2021) to offer what many within journalism believe to be the most compelling solutions. In doing so, this piece seeks to explore the underlying tension within news organizations where those tasked with using social media to engage with the public have little in common with those overseeing their efforts.…”
mentioning
confidence: 86%